Revitalization of cortical bone allograft by application of vascularized scaffolds seeded with osteogenic induced adipose tissue derived stem cells in a rabbit model - Kloeters, Oliver; Berger, Irina; Ryssel, Henning; Megerle, Kai Oliver; Leimer, Uwe; Germann, Günter (Archives of orthopaedic and trauma surgery, 2011)
Adipogenous tissue derived stem cells (ASC) are available in abundance in the human body and can differentiate in the presence of lineage-specific induction factors, for example, in myogenic, adipogenic, chondrogenic and osteogenic cells. The aim of this study was to evaluate the impact of osteogenic induced ASC’s (O-ASC) on revascularization and cellular repopulation of avital cortical bone employing a vascularized bovine scaffold.